Sistem Informasi Akademik menggunakan PHP dan MySQL pada Sekolah Tinggi Manajemen Informatika Komputer (STMIK) Indonesia Banda Aceh - Latifurrahman, Aan; Imilda; Salam, Abdus (Jurnal Sistem Komputer (SISKOM), 2023)
In this report the author discusses academic information systems using PHP and MySQL at the Indonesian Computer Information Management College (STMIK) Banda Aceh. The author designed a computer-based system which is expected to improve the current system. So it can help solve problems that often occur in data searches at the Indonesian Computer Information Management College (STMIK) Banda Aceh. The purpose of this writing is to handle student data management and make it easier to search for data quickly and precisely. The final assignment writing method uses library research, secondary archival data and internet media. The database creation process uses the HTML, PHP, CSS and SQL programming languages. The design of a web-based information system is created using a database. The database name is sisfo_akademik using 11 tables, the table names are lecturer table, identity table, department table, krs table, student table, course table, study program table, academic year table, campus table, grades transcript table, users table. In the form creation process, 14 forms are used, namely department form, study program form, course form, student form, academic year form, krs form, value input form, khs form, grades transcript form, lecturer form, user form, identity form, campus information form, login form and dashboard form. From the results of this discussion, it can be seen that designing a web-based information system will be easier to access and student data management will be better.